“ISCREVU ESTA CARTA SO PARA BOSEMESE SABER”: A DEIXIS SOCIAL EM CARTAS ROMENAS E PORTUGUESAS DA GRANDE GUERRA - MANOLE, Veronica (Studia Universitatis Babeș-Bolyai Philologia, 2022)
“I am writing this letter only for you to know”: Social Deixis in Romanian and Portuguese Letters from the Great War. This paper analyses the use of address forms in letters from World War I written by Romanian and Portuguese soldiers, with the objective of comparing the discursive configuration of the interlocutive distance (Carreira 1997) in the two languages. The analysis, based on online and printed corpus reveals systematic similarities between the two languages concerning nominal address forms: the frequent use of intensity markers (possessives, qualificative adjectives, vocatives, diminutives) to express affection towards the recipients. There are differences concerning the use of pronominal address forms. Parent-son relationships are asymmetrically constructed in both cultures, which is reflected by the use of intermediary pronouns você and dumneata, but in husband-wife correspondence only the pronoun tu is used in Portuguese, while in Romanian letters both tu and dumneata appear. In the correspondence between friends and colleagues there are some differences: the pronoun tu is used exclusively in Portuguese, while in Romanian there is an alternation between tu and dumneata. Overall, this study shows that interlocutive distance was higher in Romanian than in Portuguese at the beginning of the 20th century. Article history: Received 15 September 2022; Revised 12 November 2022; Accepted 21 November 2022; Available online 20 December 2022; Available print 30 December 2022. REZUMAT. “Scriu scrisoarea aceasta numai ca să știi”: deixisul social în scrisori românești și portugheze din Marele Război. Articolul analizează folosirea formelor de adresare în scrisori din Primul Război Mondial redactate de soldați români și portughezi, cu scopul de a compara configurarea discursivă a distanței interlocutive (Carreira 1997) în cele două limbi. Analiza bazată pe corpusuri online și tipărite arată asemănări sistematice între cele două limbi în ce privește formele nominale de adresare: folosirea frecventă a mărcilor de intensitate (posesive, adjective calificative, forme vocative, diminutive) pentru exprimarea afecțiunii față de destinatari. Sunt însă diferențe în folosirea formelor pronominale de adresare. Relațiile dintre părinți și fii sunt construite asimetric în ambele culturi, ceea ce se reflectă în folosirea pronumelor intermediare você și dumneata. Însă în corespondența dintre soți, este folosit doar pronumele tu în portugheză, în timp ce în română se folosesc pronumele tu și dumneata. În corespondența dintre prieteni sau colegi sunt diferențe: doar pronumele tu este folosit în portugheză, în timp ce în română este o alternanță între tu și dumneata. Ca o concluzie generală, acest studiu arată că distanța interlocutivă era mai mare în română decât în portugheză la începutul secolulul XX. Cuvinte-cheie: forme de adresare în portugheză; forme de adresare în română, scriere epistolară; scrisori de război; Primul Război Mondial